Non-Coding RNA Polymorphisms (rs2910164 and rs1333049) Associated With Prognosis of Lung Cancer Under Platinum-Based Chemotherapy - Chen, Yi-Xin; Chen, Juan; Yin, Ji-Ye; Zhou, Hong-Hao; He, Bai-Mei; Liu, Zhao-Qian (Frontiers in Pharmacology, 2021)
Purpose: Lung cancer is the largest cause of cancer deaths in the world. Platinum-based chemotherapy is a foundation of first-line chemotherapy. However, the prognosis of lung cancer treated with platinum-based chemotherapy is still a challenge. Single nucleotide polymorphism of non-coding RNA has the potential to be a biomarker, but its effectiveness has yet to be comprehensively assessed. In this study, we explored the association between polymorphisms of non-coding RNA and prognosis of lung cancer patients receiving platinum-based chemotherapy. Materials and Methods: For 446 lung cancer patients receiving platinum-based chemotherapy, 22 single nucleotide polymorphisms of microRNA and long noncoding RNA were genotyped by MALDI-TOF mass spectrometry. Cox regression analysis, Kaplan-Meier method, and long-rank test have been performed to assess the association of overall and progression-free survival with polymorphisms. Results: In the additive and dominant models, genetic polymorphism of ANRIL rs1333049 (G>C) was significantly associated with progression-free survival. Additive model：GG vs GC vs CC [HR=1.18, p=0.027, 95% CI (1.02-1.36)]; Dominant model: GG/GC vs CC [HR=1.28, p=0.036, 95% CI (1.02-1.60)]. In the dominant model, compared with the CC genotype patients, lower risk of death [HR=0.81, p=0.036, 95% CI (0.66-0.99)] and lower risk of progression [HR=0.81, p=0.040, 95% CI (0.67-0.99)] have been observed on the patients with CG or GG genotype in miR-146A rs2910164. Conclusion: Our research demonstrated the potential of using ANRIL rs1333049 (G>C) and miR-146A rs2910164 (C>G) as biomarkers to support the prediction of a better prognosis for lung cancer patients receiving platinum-based chemotherapy.